1991
DOI: 10.1200/jco.1991.9.5.827
|View full text |Cite
|
Sign up to set email alerts
|

Sequential high-dose methotrexate and fluorouracil combined with doxorubicin--a step ahead in the treatment of advanced gastric cancer: a trial of the European Organization for Research and Treatment of Cancer Gastrointestinal Tract Cooperative Group.

Abstract: In a prospective phase III multicenter trial, 213 patients with advanced measurable or nonmeasurable gastric cancer were randomized to receive methotrexate (MTX), fluorouracil (5-FU), and Adriamycin (doxorubicin; Farmitalia Carlo Erba, Milan, Italy) (FAMTX) or 5-FU, Adriamycin, and mitomycin (FAM). The results show a significantly superior response rate (41% v 9% [P less than .0001]), and survival (median, 42 weeks v 29 weeks [P = .004]) for FAMTX. There was a cumulative thrombocytopenia in FAM and not in FAMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
137
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(146 citation statements)
references
References 3 publications
5
137
1
3
Order By: Relevance
“…Similarly, alopecia was a rare side effect when compared with anthracyclines or etoposide-based regimens. The efficacy of this FOLFOX treatment was not different from that observed in phase II -III studies with other second-or third-generation polychemotherapy regimens in AGC (Lacave et al, 1991;Wils et al, 1991;Kelsen et al, 1992;Kim et al 1993;Rougier et al, 1994;Vanhoefer et al, 2000). Interestingly, the median TTP and OS observed in our study population are similar to those reported in a prospectively randomised study comparing ECF with the standard regimen FAMTX (Webb et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, alopecia was a rare side effect when compared with anthracyclines or etoposide-based regimens. The efficacy of this FOLFOX treatment was not different from that observed in phase II -III studies with other second-or third-generation polychemotherapy regimens in AGC (Lacave et al, 1991;Wils et al, 1991;Kelsen et al, 1992;Kim et al 1993;Rougier et al, 1994;Vanhoefer et al, 2000). Interestingly, the median TTP and OS observed in our study population are similar to those reported in a prospectively randomised study comparing ECF with the standard regimen FAMTX (Webb et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Intravenous 5FU infusion [10] or in combination with other anticancer drugs, FAM [11], FAMTX [7] have been used for chemotherapy of advanced gastric cancer. Recently, Ajani reported that DCF therapy (a combination chemotherapy using docetaxel, CDDP and 5FU) showed a significant better survival than CF (CDDP þ 5FU) therapy [12].…”
Section: Discussionmentioning
confidence: 99%
“…These results recapitulated the favorable antitumor effects and survival outcomes reported in the previous phase II study (response rate, 17/29 [59%]; MST, 322 days). 13 Considering that MSTs in other clinical trials of chemotherapy for advanced gastric cancer have ranged from 7 to 10 months, 8,[20][21][22] it appears that this regimen may yield favorable survival rates, even in clinical practice.…”
Section: Discussionmentioning
confidence: 99%